Epigenetics in pharmacogenes encoding metabolizing enzymes of second-generation antipsychotics used in schizophrenia and its clinical implications - Alvarado, Angel T.; Zavaleta, Amparo Iris; Li-Amenero, César; Bendezú, María R.; Garcia, Jorge A.; Chávez, Haydee; Palomino-Jhong, Juan J.; Surco-Laos, Felipe; Laos-Anchante, Doris; Melgar-Merino, Elizabeth J.; Bolarte-Arteaga, Mario; Tasayco-Yataco, Nesquen; et al. (Frontiers in Pharmacology, 2025)
Schizophrenia is a neuropsychiatric disorder caused by neurochemical alterations, non-genetic, genetic, epigenetic and environmental factors. Pharmacoepigenetics studies the relationship between epigenetic variability and response to drugs. The objective was to realize a descriptive review of the current state of knowledge on epigenetic molecular mechanisms in pharmacogenes encoding metabolizing enzymes of second-generation antipsychotics drugs used in schizophrenia and their clinical implications. A brief description of the pharmacogenes CYP2D6, CYP1A2, CYP2C9, CYP2C19 and CYP3A4, enzymes and metabolism of second-generation antipsychotic drugs (SGAs) such as clozapine, olanzapine, risperidone, paliperidone and quetiapine was made. The central review was on the epigenetic molecular mechanisms of DNA methylation, histone methylation and acetylation of pharmacogenes, likewise, epigenetic changes due to enzyme-inducing drugs and SGAs, and their clinical implications, were described. Despite the limited scientific literature published on the epigenetics that regulate pharmacogenes, it has been shown that DNA methylation and histone trimethylation and acetylation are the main epigenetic mechanisms in pharmacogenes, alike, some enzyme-inducing drugs would promote epigenetic changes. This review has clinical implications for the medical-clinical care and treatment of schizophrenia.